Complete Vision Loss after Laparoscopic Hysterectomy - Radtke, Steven (Case Rep Obstet Gynecol, 2021)
Postoperative vision loss (POVL) is a rare but devastating complication that has only recently been reported following laparoscopic surgery. We present the case of a 34-year-old gravida 6 para 4 female who experienced POVL following an uncomplicated laparoscopic hysterectomy. Operating time was 174 minutes, and EBL was 75 mL. After surgery, she complained of complete vision loss with no light perception. No cerebral hemorrhage or ischemia was detected on imaging. Funduscopic exam revealed no structural abnormalities. On postoperative day 7, she received an IV methylprednisolone taper. The following morning, she reported mild light perception. Later that night, she reported a partial return of visual acuity and was discharged home. At her 2-week postoperative visit, her vision had returned to baseline. POVL is an emergency and prompt evaluation should be initiated to optimize outcome.